The Influence of Leverage Capacity and Cash Reserves on Long-term Operating Performance of Mergers and Acquisitions in US - Zhang, Xinju (2018)
This paper basically investigates the influence of leverage capacity and cash reserves on long-term operating performance of acquirer firms in the US public firms after M&As. I use accounting-data based measure, create an OSL model to examine whether and how the different firms, deals, industry relativity characteristics and economic environment condition could improve post-M&As operating performance of acquirer firms in the long run. Using a sample of 760 US firms M&As deals that completed from 2000 to 2012, I find that the better historical operating performance is, the higher the firm profitability would be achieved, while leverage capacity and industry relatedness between targets and acquirers has no significant effect on improving long-term performance. Moreover, my results also suggest that prepare more cash before mergers would deteriorate post-merger operating performance of acquirers, while during financial crisis period and for cash payment deal, the influence of cash reserves could be altered, and it would have a positive significant influence on enhancing operating performance.